The Pattern of Development of Competence, Commitment, and Motivation of Teachers in Pesantren - Fauzi, Imron; Ubaidillah, Ubaidillah; Indrianto, Nino; Aminulloh, Aminulloh; Asshuwaifiyah, Uwaisah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to analyze the development of competence, commitment, and motivation of teachers in the Mu'adah Islamic boarding school. This study used a qualitative method with a multi-case type and was conducted at the Al-Amin Sumenep and Sidogiri Islamic boarding schools, Pasuruan. Data collection techniques used the instruments of the interview, observation, and documentation. Several activities in analyzing data include; data condensation, data presentation, and conclusion drawing. The results of this study found that the development of teacher competence at the Mu' Islamic boarding school is to apply a pattern based on spirituality and professionalism through integrated, holistic, and continuous coaching and training strategies, as well as to cultivate self-taught learning. The development of teacher commitment is based on the principle of devotion because Kyai, coaches, teachers, and students live together and are supported by a religiously nuanced Islamic boarding school environment. The development of teacher motivation is based on the values of sincerity and blessing combined with modern professional management.